2021
DOI: 10.3390/biology10090910
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of Adjuvant Chemotherapy on Cardiovascular Responses and Exercise Tolerance in Patients with Early-Stage Breast Cancer

Abstract: Background: Adjuvant chemotherapies are commonly used for treating early-stage breast cancer. However, whether chemotherapeutic regimens affect exercise tolerance and cardiovascular responses remains unclear. Therefore, we investigated the effects of receiving CAF and AC-T on exercise tolerance and cardiovascular responses in patients with early-stage breast cancer. Methods: Thirty-four patients with breast cancer (age: 44 ± 1 years; stage I-II) received either CAF (n = 15) or AC-T (n = 19), depending on clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Chemotherapy causes heart damage, and Lin et al found that chemotherapy further limits exercise capacity in patients with early-stage breast cancer. Basic information on various cardiovascular responses to exercise after chemotherapy in patients with early breast cancer [ 32 ]. Schoffel et al also believe that chemotherapy can easily cause heart failure from the adverse effects of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy causes heart damage, and Lin et al found that chemotherapy further limits exercise capacity in patients with early-stage breast cancer. Basic information on various cardiovascular responses to exercise after chemotherapy in patients with early breast cancer [ 32 ]. Schoffel et al also believe that chemotherapy can easily cause heart failure from the adverse effects of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most cancer patients who suffer from fatigue and muscle weakness are encouraged to rest and avoid exercise to reduce fatigue and improve pain symptoms (Courneya & Friedenreich, 2007). In recent decades, the use of exercise programs as an effective intervention to improve the quality of life of cancer patients has attracted the attention of scientists (Lin et al, 2021;Mujtaba, Mazhar, & Tanzeel, 2021). Many studies have been conducted on the effect of physical activity on various diseases (Courneya & Friedenreich, 2007) but there are limit studies about effect of physical activity on ALL.…”
Section: Introductionmentioning
confidence: 99%